Pengaruh Inovasi Produk dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Bank BNI Kantor Cabang UGM Yogyakarta dengan Kepuasan Nasabah sebagai Variabel Mediasi - Sari, Cindy Kartika; Mursyid, Mursyid; Fahlefi, Wilis (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2024)
The aim of this research is to determine the effect of product innovation and service quality on customer loyalty at Bank BNI KC UGM Yogyakarta with customer satisfaction as a mediating variable. The research was carried out by distributing questionnaires to 100 respondents who were customers of Bank BNI KC UGM Yogyakarta. The data that was collected was then processed to determine the relationship between the research variables using SmartPLS software version 3.2.9. Based on the research results, information was obtained that 1) product innovation has a significant effect on customer loyalty at Bank BNI KC UGM Yogyakarta; 2) service quality has a significant effect on customer loyalty at Bank BNI KC UGM Yogyakarta; 3) product innovation has a significant effect on customer satisfaction at Bank BNI KC UGM Yogyakarta; 4) service quality has no significant effect on customer satisfaction at Bank BNI KC UGM Yogyakarta; 5) product innovation has a significant effect on customer satisfaction and customer loyalty at Bank BNI KC UGM Yogyakarta; 6) service quality has no significant effect on customer satisfaction and customer loyalty at Bank BNI KC UGM Yogyakarta; and 7) customer satisfaction has a significant effect on customer loyalty at Bank BNI KC UGM Yogyakarta.